DISTRIBUTION AND TROPHIC ASSOCIATIONS OF ANT GENUS MONOMORIUM MAYR, 1855 (HYMENOPTERA: FORMICIDAE: MYRMICINAE) WITH APHIDS IN POTHWAR REGION OF PAKISTAN - M. T. Rasheed; I. Bodlah1; A. Gull-e-Fareen; H. Ali; M. A. Bodlah4and M. U. Raja (Journal of Animal and Plant Sciences, 2020)
Two species of genus Monomorium Mayr, 1855 namely Monomorium indicum Forel, 1902 and Monomorium sagei Forel, 1902 have been recorded for the first time from Pothwar region of Pakistan. Currently a total of five species of this genus have been documented from Pakistan. Conservation status of two newly recorded species has also been discussed. Both species have been described here using Bingham (1903). Morphological characters of prosoma, mesosoma and metasoma were used for the identification of the species. Description has been supported with micrographs of identification characters, morphometric, world distribution and GPS coordinates of Pakistan. Trophic associations of both species with aphid partners are also reported for the first time from Pakistan. M. indicum was found to be associated with 2 aphid species namely, Aphis gossypii Glover, 1877 and Aphis fabae Scopoli, 1763 while M. sagei lived in associations with Greenidea (Trichosiphum) psidii van der Goot, 1917, Aphis gossypii, A. fabae and A. fabae solanella Theobald, 1914.
Keywords: Monomorium; Myrmicinae; Aphid associations; Pothwar; Pakistan